HIERARCHY OF HUMAN NEEDS ON RACHEL WARD'S NUMBER - Rudyanto Rudyanto; Apsari Fajar Prifantini; Siti Nur Hidayah (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
This study analyses novel entitled of the novel is “Number” by Rachel Ward. Therefore, the writer is interested to conducting research to know human needs in Rachel Wards Number. By using a psychological approach to analyse psychological problems in Rachel Ward''s novel entitled Number .It is a novel that tells how the psychological aspect of Jem when he knows when someone will die and is related to his love relationship with Spyder who was the accused in the London Eyes bombing, but not Spyder. In this study, the researcher completed the data using a descriptive analysis approach. This qualitative descriptive method was used to analyze and interpret the data, and the information was gathered in the form of words, text, and explanations instead of a number. This approach aims to explain how is human needs Rachel Ward‟s novel “Numbers”In this study, the writer presents data analysis based on five types of Human Needs in Rachel Ward''s novel